Production of aroma compounds by degradation of carotene from crude palm oil - Abd Hamid, Hazrulrizawati (2016)
Carotenoids derived aroma compounds such as α-ionone, β-ionone, β-damascenone and other few important compounds can be produced via degradation. These aroma compounds have a heavy demand in food products, cosmetics and pharmaceutical industry. Currently, there are growing concerns from consumers particularly about the source of ingredients and awareness about potentially harmful synthetic compound. These have made the global demand for naturally produced aroma compounds increases gradually and gained renewed attention recently. However, extraction of natural carotenoid-derived aroma compounds directly from natural sources is expensive and not economical because isolation of single pure natural aroma compounds directly from plant sources is difficult and involves tedious work as it is present in a very low yield. Therefore, this research which is aims to produce aroma compounds from degradation of carotenoids from CPO and oil palm wastes (OPW) was conducted. The palm carotene extraction process was performed using soxhlet adsorption, adsorption column chromatography, saponification, neutralisation and transesterification for CPO and SFE and soxhlet extraction for OPW of PPF and EFB. The extraction process is mainly aimed in extracting palm carotene rich in β-carotene concentration. In comparison with all the extraction techniques, soxhlet adsorption using HP-20 as adsorbent resulted high concentration of β-carotene extracted which was 3856 ppm of 77.12 % at 1:4 ratio of CPO: HP-20 for 1 hr IPA extraction time. The concentration of β-carotene extracted was calculated by using HPLC standard calibration curve. As for the production of aroma compounds, optimization of degradation reaction was carried out using commercial β-carotene in order to achieve optimum degradation conditions. For the optimization of thermal degradation reaction, different sonication time, reaction time and reaction temperature were studied. While for oxidative degradation, effect of sonication, light and amount of catalyst were studied. Based on the result obtained, the optimum condition for thermal degradation was 1 hr sonication, 5 hr reaction and 120-130 ◦C whereas for oxidative degradation vial must be completely covered, sealed and kept at room temperature. Then, the extracted palm carotene was degraded using thermal and oxidative degradation under optimized reaction conditions. The oxidative degradation using extracted carotene failed to produce any aroma compounds. However, thermal degradation of extracted carotene from both CPO and OPW produced aroma compounds such as β-ionone, DHA, 2,4-decadienal, D-limanone, β-epoxide, and 3-oxo-β-ionone. The major aroma compound with highest composition produced was DHA (37.26 %) followed by β-ionone (9.23 %) analysed by using GC-MS and GC-FID. The results obtained proved that production of aroma compounds by degradation of β-carotene from CPO and OPW is viable. As there is no study was carried out on production of aroma compounds by degradation of carotenoids from these sources, this study is believed could support the current demand of natural aroma compounds and found to be energy and a cost saving method also quality and environment friendly. Further works are still required to completely isolate β-carotene and understands the mechanism involved in degradation reaction to make this effort applicable in industry scale.